2020
DOI: 10.1088/1757-899x/736/2/022044
|View full text |Cite
|
Sign up to set email alerts
|

Integrated production of prebiotic xylooligosaccharides and high value cellulose from oil palm biomass

Abstract: Oil palm empty fruit bunch (OPEFB) fibre, which is the byproduct of fruits being stripped from the fresh fruit bunch in palm oil mill, was evaluated in terms of the production of xylooligosaccharides (XOs) and the solid residue was treated for cellulose recovery. Chemoenzymatic hydrolysis that consists of chemical fractionation of OPEFB fibre to isolate xylan with further enzymatic hydrolysis to XOs in a packed bed column reactor (PBCR) was performed. An immobilised xylanase of Thermomyces lanuginosus at the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Cellulose degradation process occurs on temperatures 280-320°C [13]. Total acid obtained in this study is high due to the cellulose contained in OPF (40 -50%) [19]. Different temperatures and times affect acetic acid content in liquid smoke.…”
Section: Acetic Acid Contentmentioning
confidence: 69%
“…Cellulose degradation process occurs on temperatures 280-320°C [13]. Total acid obtained in this study is high due to the cellulose contained in OPF (40 -50%) [19]. Different temperatures and times affect acetic acid content in liquid smoke.…”
Section: Acetic Acid Contentmentioning
confidence: 69%
“…Each OPT consists of lignocellulosic components; cellulose (22%-44%), hemicellulose (Hc) (12%-44%), and lignin (18%-36%). 6 The mechanical characteristics of Hc films derived from various biomass sources range significantly. Owing to its branching and amorphous architectures, unmodified Hc films frequently exhibit poor mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study done by Fatimah Mhd Ramle, 5 who studied about chemical composition of parenchyma and vascular bundle from Elaeis guineensis , found that parenchyma cells of the OPT consist of high starch and low lignin content. Each OPT consists of lignocellulosic components; cellulose (22%–44%), hemicellulose (Hc) (12%–44%), and lignin (18%–36%) 6 . The mechanical characteristics of Hc films derived from various biomass sources range significantly.…”
Section: Introductionmentioning
confidence: 99%